UJI AKTIVITAS ANTI BAKTERI EKSTRAK ETANOL 96% DAUN TEH-TEHAN (Acalypha siamensis) PADA BAKTERI Escherichia coli DENGAN MENGGUNAKAN METODE CAKRAM - Dina Maya Syari; Patriza, Zahra Sukma (Universitas Imelda Medan, 2022)
Teh-tehan (Acalypha siamensis) is a plant that has many branches including a bush with a height of 1-2 m. Escherichia coli bacteria can be found in the human intestine, most of these bacteria are harmless, but some can cause serious poisoning in humans such as diarrhea. The purpose of this study was to determine the antibacterial activity of the ethanol extract of tea-tea leaves (Acalypha siamensis) against Escherichia coli bacteria using the disc method. This research is descriptive by using the ratio of the extract concentration of 20%, 30%, 50%, and 80% with a positive control of chloramphenicol and a negative control of aquadest. he results showed that the concentration of ethanol extract had antibacterial activity. Escherichia coli bacteria gave the highest inhibition zone at a concentration of 80% with an inhibition zone diameter of 12.8 mm while the control chloramphenicol was 28.5 mm. Based on the ANOVA data analysis test that there is a significant difference in antibacterial inhibition.